PERKEMBANGAN HASIL PEMERIKSAAN BADAN USAHA MILIK NEGARA (BUMN) PERIODE 2011-2013 - Firmansyah Firmansyah (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2014)
This research is an explorative research in order to get a description on the findings of the examining result on the finance and performance report and this examination with the specific goal at Badan Usaha Milik Negara (BUMN) in the periode of 2011-2013. From the findings, it is got the description on the management of the country wealth at BUMN in the periode 2011-2013. It showsthe progressis not good, especially based on the performance examination and the examination with the specific good. On the performanceexamination is got that the object examined keeps on decreased but the amount of cases found and the rate of the finance loss increase rapidly each year. For the examination on specific goal shows that there are amounts of cases fluctuative findings but with the rapid loss rate. The repairment on the internal control system (SPI) applied at BUMN in Indonesia need to be done, because eventough in some cases, the weakness of SPI does not cause the finance loss directly.